Photocatalytic degradation process of waste water using titanium dioxide as catalyst - Mohd Afendi, Abdul Mutalib (2009)
Photocatalytic degradation is a process where the organic contaminant in water is degraded by UV light. UV photo oxidation acts to degrade and remove organic compound through the ultraviolet radiation to activate the catalyst. The catalyst used in this study is titanium dioxide (TiO2) which is chosen based on its properties that are low toxicity, low resistance to corrosion and semiconductor. The semiconductor will absorb the UV light and attract electrons across the energy gap into the conduction band. This electron will change into hydroxyl radicals which can decompose organic compounds while still in the waste water stream. So this is the basic concept that applied in industrial to treat the waste water or any pollutant in water in order to protect the environmental. Simulated oils waste water was used to replicate the Palm Oil Mill Effluent (POME). The studied parameters are the effect of catalyst concentration and irradiation time. The effect of both parameters has studied using Design Expert 7 to determine the optimum condition of degradation activities. The degradation activities were measured through the change of initial and final COD and dissolved oxygen in sample. Through Analysis of Variance (ANOVA) and optimization application of Design Expert 7, it was found that the optimum condition to achieve maximum degradation activities.